2023
DOI: 10.1039/d3fo01116j
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa flavanol supplementation preserves early and late radial artery function after transradial catheterization

Abstract: Background: The transradial approach for coronary angiography is associated with fewer complications and preferred over the femoral approach. Injury to the radial artery (RA) endothelium elicits intimal hyperplasia, possibly resulting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…25 Recently, we showed that the intake of 1000 mg of cocoa flavanols (160 mg (−)-epicatechin) protects radial arteries against intima hyperplasia after catheterization-induced injury. 26 We hypothesized, that CF at a dose sufficient to maximally increase endothelial function have a positive impact on peakVO 2 and exercise capacity in older adults without manifest cardiovascular disease. Therefore, the aim of the current study was to investigate the effect of dietary CF intake on cardiorespiratory fitness and functional status in healthy elderly individuals.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, we showed that the intake of 1000 mg of cocoa flavanols (160 mg (−)-epicatechin) protects radial arteries against intima hyperplasia after catheterization-induced injury. 26 We hypothesized, that CF at a dose sufficient to maximally increase endothelial function have a positive impact on peakVO 2 and exercise capacity in older adults without manifest cardiovascular disease. Therefore, the aim of the current study was to investigate the effect of dietary CF intake on cardiorespiratory fitness and functional status in healthy elderly individuals.…”
Section: Introductionmentioning
confidence: 99%